Dental sectioning for intraoral equine cheek teeth extractions: 29 cases - Alexis Leps; Szabolcs Korsos; Michèle Clarysse; Lieven Vlaminck (Frontiers in Veterinary Science, 2024)
The objectives of this retrospective study were to describe cheek teeth extraction by the sectioning technique, the decision making to use this technique and its potentially associated complications. Sectioning for dental extraction purpose was used in 29/461 (6.3%) of cases. Oro-sinusal fistula was the main post-operative complication, with 4/29 (13.7%) cases developing a macroscopic communication between the alveolus of the tooth extracted and the adjacent sinus compartment. All teeth where sectioning was attempted were successfully extracted. Sectioning for dental extraction appears to be a safe technique that can be used instead of or in addition too other minimal invasive cheek teeth extraction techniques. Thorough preoperative planning including oroscopic examination and medical imaging modalities are required to help in decision making, as well as excellent sedation and analgesia and horse compliance.